Inequality and Growth Revisited - Robert J. Barro (Asian Development Bank (ADB), 2008)
This paper updates and extends the work of Barro (2000). International data confirm the presence of the Kuznets curve-an inverse-U shape relationship between income inequality and per capita GDP-that is relatively stable from the 1960s into the 2000s. The direct effect of international openness on income inequality is also found to be positive. On the other hand, a cross-country-growth equation shows a negative effect of income inequality on economic growth, holding fixed a familiar set of other explanatory variables. This effect diminishes as per capita GDP rises and may be positive for the richest countries.
hdl:11540/1762
Keywords: I31; O47; 330; inequality; growth; Kuznets curve; Gini coefficient